An Analytical Model for the Plastic Bending of Anisotropic Sheet Materials, Incorporating the Strain-Hardening Effect - Yaroslav Erisov; Alexander Kuzin; Andry Sedelnikov (Technologies, 2024)
This study develops an analytical model for the plastic bending of anisotropic sheet materials, incorporating strain-hardening effects. The model, experimentally validated with aluminum alloy samples and digital image correlation, accurately predicts stress–strain distributions, bending moments, and thinning behavior in the bending processes. The results reveal that while plastic anisotropy significantly increases the strain intensity, enhancing it by up to 15% on the inner surface relative to the outer under identical bending radius, it does not affect the position of the neutral layer. Strain hardening, on the other hand, raises the bending moment by approximately 12% and contributes to material thinning, which can reach 3% at smaller bend radii. Furthermore, quantitative analysis shows that decreasing the bend radius intensifies the strain, impacting the final geometry of the workpiece. These findings provide valuable insights for optimizing die design and material selection in forming processes involving anisotropic materials, enabling engineers to more precisely control the force requirements and product dimensions in applications where accurate bending characteristics are critical.